Performance Comparison of Saliency Detection - Ning Li; Hongbo Bi; Zheng Zhang; Xiaoxue Kong; Di Lu (Advances in Multimedia)
Saliency detection has attracted significant attention in the field of computer vision technology over years. At present, more than 100 saliency detection models have been proposed. In this paper, a relatively more detailed classification is proposed. Furthermore, we selected 25 models and evaluated their performance using four public image datasets. We also discussed common problems, such as the influence to model performance by prior information and multiple objects. Finally, we offered future research directions.